Higher Food Prices in Sub-Saharan Africa - Wodon, Quentin (World Bank, 2012)
The spike in global food prices in 2008 led to significantly higher food prices across the developing world. Global commodity prices have since fallen but remain volatile, and local food prices remain high in many countries. The authors review the evidence on the potential impact of higher food prices on poverty, focusing on Sub-Saharan Africa, and examine the extent to which policy responses are able to protect the poor. They show that rising food prices are likely to lead to higher poverty in Sub-Saharan Africa as the negative impact on net consumers outweighs the benefits to producers. A recent survey shows that the most common policy response in Sub-Saharan African countries in 2008 was reducing taxes on food, while outside the region subsidies were the most popular measure. Sub-Saharan African countries also have a higher prevalence of food-based safety net programs, some of which were scaled up to respond to rising prices. The review suggests that the benefits from reducing import tariffs on staples are likely to accrue largely to the nonpoor. Safety net programs can be more effective, but geographic targeting and other investments to strengthen safety nets are necessary to ensure that fewer people are affected by future crises.